Developing genre and pragmatic competence through service-learning: a discourse-based study in a Vietnamese transnational hospitality ESP programme - Tuan, Nguyen Nhat; Ha, To Ngan; Duong, Vu Thuy; Huyen, Vu Thi (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examines how service-learning supports the development of genre awareness and pragmatic competence among Vietnamese hospitality students in an English for Specific Purposes programme. Conducted in the Vietnamese context as part of a transnational bachelor’s degree programme, the research adopts a qualitative multiple-case design, drawing on learner-produced texts, recorded service interactions, reflective journals, and stimulated recall interviews. Anchored in genre theory and interlanguage pragmatics, the study investigates how learners engage with professional tourism genres, enact speech acts in authentic communicative situations, and reflect on their language use. The findings reveal that service-learning facilitates uptake of genre-specific discourse structures, encourages the use of context-sensitive pragmatic strategies such as mitigation and repair, and fosters metapragmatic awareness through structured reflection. Nonetheless, challenges remain in sustaining register consistency, managing intercultural framing, and aligning performance with professional discourse norms. The study concludes that service learning, when integrated with explicit linguistic scaffolding, constitutes a productive environment for applied language development in ESP. It advocates for further discourse-analytic inquiry into learner language use in situated, multilingual settings.